Acid-induced Zn(ii)-based metal–organic frameworks for encapsulation and sensitization of lanthanide cations1. Issue 11 (21st March 2015) - He, Hongjie; Zhang, Lina; Deng, Mingli; Chen, Zhenxia; Ling, Yun; Chen, Jinxi; Zhou, Yaming
<x xml:space="preserve">Abstract</x> Two Zn(ii)-based metal–organic frameworks with different coordination geometries have been synthesized and one can effectively capture metal cations and sensitize the visible-emitting Tb3+.